Website files: medievalromance.bodleian.ox.ac.uk - Systems and Services, B (University of Oxford, 2020)
This is a closed internal dataset containing websites files relating to medievalromance.bodleian.ox.ac.uk. These files were archived as part of the LIB702 Web Application Rationalisation Project (2019-2020) ran by Bodleian Digital Library Systems and Services. Due to the size of the site the files could not be saved to the GitLab LegacySite project space (https://gitlab.bodleian.ox.ac.uk/legacysites). The ORA UUID relating to this record has instead been added to GitLab to enable retrieval if necessary.